PELUANG DAN TANTANGAN PRODUK FINTECH LENDING SYARIAH (PEER-TO-PEER LENDING SYARIAH) BERIZIN OTORITAS JASA KEUANGAN UNTUK MENINGKATKAN KESEJAHTERAAN EKONOMI MASYARAKAT: STUDI LITERATUR - Yati, Alan (Jurnal GeoCivic, 2024)
This study aims to identify the opportunities and challenges of sharia fintech lending in improving the welfare of the micro economy of the underprivileged, with a focus on sharia financing products registered with the Financial Services Authority (OJK). Sharia fintech lending, as an innovation in the financial sector, offers wider and fairer access to financial resources for the underprivileged, in accordance with sharia principles that avoid usury, gharar, and maysir. The research methodology used in this study uses qualitative research methods. This type of research is library research. This type of research is library research which is descriptive analytical. The data collection method uses primary data and secondary data. This study examines the opportunities and challenges of sharia fintech lending to help overcome the problem of community economic welfare. This study found that sharia fintech lending has great potential for and improves the economic welfare of the community. However, there are various obstacles that need to be overcome, obstacles such as product competition with Conventional Fintech, and Low levels of financial literacy and technological innovation are the main concerns.